“I Looked It Up in DeepL”: Machine Translation and Digital Tools in the Language Classroom - Cotelli Kureth, Sara; Delorme Benites, Alice; Haller, Mara; Noghrechi, Hasti; Steele, Elizabeth (Venise: Edizioni Ca'Foscari, 2023)
This article looks at a widespread yet erroneous use of machine translation (MT): looking up single words, thus treating MT systems as online bilingual dictionaries (ODs). After a literature review of this trend in research about MT, we consider data from a large survey that we carried out in 2021 at all Swiss universities on MT use and users’ attitudes. When analysing users’ metalinguistic awareness, we discovered that nontranslators perceive the text to translate, mostly at word level, leading to the misuse of MT systems as ODs. Moreover, the survey results revealed confusion between the different digital tools for language learning, namely MT, online parallel corpora like Linguee and ODs. We therefore suggest broadening the scope of MT literacy to include training learners in general digital literacy to enable them to use such tools appropriately.
Keywords: traduction automatique; enseignement/apprentissage des langues; dictionnaires en ligne; corpus en ligne; outils d'apprentissage